1983
DOI: 10.1111/j.1365-2125.1983.tb05878.x
|View full text |Cite
|
Sign up to set email alerts
|

Antidepressant drugs, convulsions and epilepsy.

Abstract: 1 Evidence concerning the convulsant effects of non-monoamine oxidase inhibitor antidepressant drugs has been reviewed. 2 Mianserin is convulsant in therapeutic doses but seizures have not been reported following overdose. 3 The convulsant effects of mianserin are probably no greater than for other non-monoamine oxidase inhibitor antidepressant drugs. 4 Enzyme-inducing anti-epileptic drugs can reduce the peak plasma concentration of mianserin and shorten its elimination half-life, probably by inducing its me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

1984
1984
2022
2022

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(2 citation statements)
references
References 22 publications
0
2
0
Order By: Relevance
“…It is difficult to estimate whether this is a good reflection of the situation in the clinic. According to Richens et al [1983] there have been only a few reports of seizures fol lowing mianserin. Edwards and Glenn-Bott [1983] on the other hand conclude from clinical data that mianserin should be rated as high as amitriptyline and higher than imipramine concerning its (pro)convulsive activity.…”
Section: Discussionmentioning
confidence: 99%
“…It is difficult to estimate whether this is a good reflection of the situation in the clinic. According to Richens et al [1983] there have been only a few reports of seizures fol lowing mianserin. Edwards and Glenn-Bott [1983] on the other hand conclude from clinical data that mianserin should be rated as high as amitriptyline and higher than imipramine concerning its (pro)convulsive activity.…”
Section: Discussionmentioning
confidence: 99%
“…The use of antidepressant drugs in epileptic patients has been a concern of clinicians because of reports that these drugs have proconvulsant or frank convulsant effects (Toone and Fenton, 1977;Trimble, 1978;Richens et al, 1983;Edwards et al, 1986). However, selective serotonin-uptake inhibitors, a relatively recent class of antidepressant drugs (Lemberger et al, 1985), have been reported to potentiate the anticonvulsant effects of the serotonin precursor, 5-hydroxytryptophan (SHTP), in mice (Buus Lassen, 1978).…”
mentioning
confidence: 99%